2022
DOI: 10.3390/ijms232113401
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review on Platelets and Tumor Angiogenesis: Do We Need More Evidence or Better Analysis?

Abstract: Platelets are an active component of the tumor microenvironment (TME), involved in the regulation of multiple tumor processes, including angiogenesis. They are generated rich in angiogenic factors in their granules to actively participate in the hemostatic process by megakaryocytes and further enriched in angiogenic factors by all components of the tumor microenvironment to control the angiogenic process because of their preferential relationship with the endothelial component of vessels. In recent decades, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Also, there was a statistically significant positive correlation between IL- 35 serum level and platelet count. This could be attributed to the active role of platelets (rich in angiogenic factors in their granules) in the tumor microenvironment (TME), being involved in tumor angiogenesis as they are rich in angiogenic factors in their granules [ 33 ]. Similarly, IL-35 promotes tumor angiogenesis and tumor cell expansion through inducing the formation of VEGF [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, there was a statistically significant positive correlation between IL- 35 serum level and platelet count. This could be attributed to the active role of platelets (rich in angiogenic factors in their granules) in the tumor microenvironment (TME), being involved in tumor angiogenesis as they are rich in angiogenic factors in their granules [ 33 ]. Similarly, IL-35 promotes tumor angiogenesis and tumor cell expansion through inducing the formation of VEGF [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that platelets secrete pro-angiogenic cytokines, including vascular endothelial growth factor and endothelial cell growth factor, which promote tumor angiogenesis. 38,39 Furthermore, peripheral platelets facilitate the invasiveness of circulating tumor cells by covering them in a P-selectin-dependent mechanism, thereby preventing natural killer (NK) cell-mediated tumor cell apoptosis. 39 Prior researches have indicated that levels of NLR, PLR, and MLR are linked to the prognosis of patients with gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Megakaryocytes that migrate to the blood vessels of lung cancer tissue produce more platelets, helping tumor cells break through the endothelial barrier to achieve transendothelial migration and thus promoting the development and metastasis of lung cancer [ 64 ]. In early stage of lung cancer, increased expression of thrombospondin-1 (TSP-1) in lung megakaryocytes and platelets inhibits endogenous angiogenesis and exerts antitumor effects [ 65 ]. However, pulmonary megakaryocytes secrete platelet factor 4 (PF4), which in turn promotes hematopoietic function and megakaryocyte production under stress conditions caused by chemotherapy and radiotherapy [ 66 ], accelerating tumor growth.…”
Section: Megakaryocytes and Platelets Are Associated With Lung Injurymentioning
confidence: 99%